Mother–Infant Dyadic State Behaviour: Dynamic Systems in the Context of Risk. Issue 3 (5th May 2015) - Coburn, Shayna S.; Crnic, Keith A.; Ross, Emily K.; Lunkenheimer, Erika S.; Leerkes, Esther M.
<x xml:space="preserve">Abstract</x> Dynamic systems methods offer invaluable insight into the nuances of the early parent–child relationship. This prospective study aimed to highlight the characteristics of mother–infant dyadic behavior at 12 weeks post‐partum using state space grid analysis (total n = 322). We also examined whether maternal prenatal depressive symptoms and perceived stress were associated with reduced non‐negative engagement in exchange for more negativity and unengagement, and contrasted them with global observational methods. Non‐negative engagement (NNE) was an attractor for dyads during a teaching task, with a range of flexibility and entropy across dyads. Further, dyads with mothers reporting higher prenatal depressive symptoms demonstrated less 12‐week NNE dyadic behavior and more dyadic negativity. Prenatal maternal perceived stress was associated with reduced negativity and reduced flexibility in NNE states. However, maternal distress of any kind was not associated with entropy of behavior. Finally, direct comparisons with global perspectives of dyadic behavior indicated strong external validity relating to concepts of dyadic affect and engagement, and dynamic approaches remained uniquely related to prenatal distress above and beyond global observations of behavior. Findings lend support to the utility and necessity of dynamic systems approaches for identifying mechanisms of prenatal risk and emerging parent–child social–emotional functioning. Copyright © 2015 John Wiley & Sons, Ltd.